Comparative Uterotrophic Effects of Endoxifen and Tamoxifen in Ovariectomized Sprague Dawley Rats - Schweikart, Karen M.; Eldridge, Sandy R.; Safgren, Stephanie L.; Parman, Toufan; Reid, Joel M.; Ames, Matthew M.; Goetz, Matthew P.; Davis, Myrtle A. (2014)
Endoxifen (4-hydroxyl-N-desmethyl tamoxifen), one of the major active metabolites of tamoxifen, has substantially greater estrogen antagonist properties and antiproliferative effects in breast tumor cells than tamoxifen, a mixed estrogen agonist/antagonist. An associated risk of endometrial cancer and hyperplasia has been linked to the estrogen agonist properties of tamoxifen. We evaluated endoxifen using a classic uterotrophic effects method. Rats were given endoxifen or tamoxifen orally for three days. Estradiol was the positive control. Endoxifen and tamoxifen plasma levels exceeded those previously observed clinically. Uterine weight was three-fold higher in the estradiol group than in the tamoxifen or endoxifen groups, which did not differ from vehicle controls. Tamoxifen and endoxifen caused a greater increase in luminal epithelial cell height than estradiol. Both tamoxifen and endoxifen produced an increase in the stromal BrdU labeling index (LI) that was ≤ estradiol and inversely related to dose, but did not affect luminal epithelial cell BrdU LI. As expected, estradiol increased luminal epithelial cell proliferation. These results indicate that endoxifen induces uterotrophic effects, but is less potent than estradiol in eliciting these effects. Given prior preclinical observations that endoxifen has superior antitumor activity than tamoxifen, the observations of similar uterine effects suggest that the endoxifen risk/benefit ratio may be superior to tamoxifen.